use the matrix swot analysis to show” Strength- weaknesses/opportunities-threats in multinational companies case study” MCDONALDS - amel bensotra; nawal chicha (Journal of Excellence for Economics and Management Research, 2021)
The importance of the present study comes from the importance of its topic.The aim of this research paper is to address and highlight the role of using the SWOT as an analysis tool by multinational companies. Furthermore, to achieve this aim, this study relied upon previous studies which dealt with the topic.On this basis, the study followed the descriptive and analytical approach which was relied upon in order to identify the strengths, weaknesses, opportunities and threats. In addition to that, the study also aims to identify the persistence of these companies on the international level. As a conclusion, the most important role of using the SWOT as an analysis tool in multinational companies is the contribution  it  offers to know the strategy  adopted by those companies